(untitled) (Research, Society and Development, 2022)
To evaluate the temporal tendency of work bonds for professional nurses in the southeast region during the period from 2003 to 2018. This is an ecological study of temporal tendency using data obtained through a public database. if the trend of nurses’ bond generation during the period from 2003 to 2018, using polynomial equations using the resources of the statistical software R. A significant trend was considered when the p-value ≤ 0.05. From the construction of the time line, the stationary trend in the generation of bonds for nurses in the Southeast region was identified with a significant drop in bonds registered in the period. The stationary trends observed in the southeast region reveal a possible stagnation of jobs for nurses. This scenario can influence safe and quality nursing care since the reduction of the contracted workforce can generate intensification and overload of those in the market.